Synthesis, Characterization and Preliminary Antimicrobial Study of Some New Ether and Thioether Derivatives of Sulfadiazine - Mohammed Kamil Hadi; Maadh Qusay Abdulkadir; Oleiwi, Mohammed Abdulameer; Sarah Ahmed; Zainab Dhia Kamms (Iraqi Journal of Pharmaceutical Sciences, 2025)
A new series of ether and thioether derivatives of sulfadiazine (T1-T3 and E1-E3) have been synthesized from reaction of sulfadiazine with chloroacetyl chloride and the resultant compounds treated with different phenols and thiols. The structures of target ether and thioether derivatives were confirmed depending on their analytical and spectral data. The antimicrobial effect of the final derivatives has been tested in vitro with gram-positive and gram-negative bacteria and candida albicans. The antibacterial activity of the target compounds after three days of incubation demonstrated that all the evaluated derivatives exhibited superior antibacterial activity in comparison with amoxicillin and ciprofloxacin against all tested bacteria.